2003
DOI: 10.1128/jcm.41.1.44-49.2003
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Mycobacterium avium Genotypes with Distinctive Traits by Combination of IS 1245 -Based Restriction Fragment Length Polymorphism and Restriction Analysis of hsp65

Abstract: One-hundred eight Mycobacterium avium isolates from pigs, humans, birds, and bovines were typed by the IS1245-based restriction fragment length polymorphism (RFLP) method and PCR-restriction enzyme analysis (PRA) of hsp65. Nine clusters of isolates showing more than 80% similarity in their RFLP profiles were detected. The largest cluster (cluster B) included 32 of 79 pig isolates (40.5%), 3 of 25 human isolates (12%), and 1 of 2 bovine isolates, comprising 33% of all isolates. The second largest cluster (clust… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
24
0
2

Year Published

2004
2004
2014
2014

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 25 publications
1
24
0
2
Order By: Relevance
“…Human immunodeficiency virus coinfection information was available for some, but not all, of the isolates. The isolates are summarized in Table 1 and were originally isolated and archived from other studies (2,5,6,13,17,18,23).…”
Section: Methodsmentioning
confidence: 99%
“…Human immunodeficiency virus coinfection information was available for some, but not all, of the isolates. The isolates are summarized in Table 1 and were originally isolated and archived from other studies (2,5,6,13,17,18,23).…”
Section: Methodsmentioning
confidence: 99%
“…The bird strains belong to the serovar 1, 2, or 3 and contain IS901 (2, 16). They also have an identical three-banded pattern with the standardized IS1245 RFLP, often referred to as the "birdtype" profile (1,11,13,16). The bird strains in the present study showed the same three-banded pattern with the standardized long IS1245 probe (Fig.…”
mentioning
confidence: 99%
“…La variante I de M. avium se ha encontrado con mayor frecuencia asociada con infección diseminada en pacientes con sida mientras que las variantes II y III han sido descritas con mayor frecuencia en muestras ambientales (11). Estos hallazgos sugieren que las variantes PRA de M. avium pueden diferir en cuanto a su virulencia y transmisibilidad (12).…”
unclassified